2005
DOI: 10.1007/s11095-004-9020-4
|View full text |Cite
|
Sign up to set email alerts
|

How Much Particle Surface Corrugation Is Sufficient to Improve Aerosol Performance of Powders?

Abstract: Powders with varying degrees of corrugation were successfully obtained by spray drying with their surface roughness quantified by fractal analysis. It was shown that only a relatively small degree of surface corrugation was sufficient to accomplish a considerable improvement in the aerosol performance of the powder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(123 citation statements)
references
References 23 publications
11
110
2
Order By: Relevance
“…As example, GISO3-leu15 formulations, containing 15% w/w of leu and obtained from 30% v/v of ISO/water feed, emitted 50.4 mg of fine G after one actuation of the Turbospin device. These results are in agreement with previous studies [29,30,53] evidencing the enhancement of powder aerosol performance as particle surface corrugation goes up to a certain degree; further corrugation enhancement did not improve aerodynamic properties. The plot in figure 13 allows to appreciate a dramatic increase in both particle corrugation (SEM micrographs) and FPF as the leu content increased.…”
Section: Aerodynamic Behavior Of G/leu Powderssupporting
confidence: 93%
See 1 more Smart Citation
“…As example, GISO3-leu15 formulations, containing 15% w/w of leu and obtained from 30% v/v of ISO/water feed, emitted 50.4 mg of fine G after one actuation of the Turbospin device. These results are in agreement with previous studies [29,30,53] evidencing the enhancement of powder aerosol performance as particle surface corrugation goes up to a certain degree; further corrugation enhancement did not improve aerodynamic properties. The plot in figure 13 allows to appreciate a dramatic increase in both particle corrugation (SEM micrographs) and FPF as the leu content increased.…”
Section: Aerodynamic Behavior Of G/leu Powderssupporting
confidence: 93%
“…In fact, previous reports suggested that improvement of the respirable fraction may be obtained not only by lowering the size or the density of a powder, but also reducing interparticulate cohesion [29,30]. Corrugated particles might also be more appropriate for dissolution in the lung fluid due to a larger area.…”
Section: Naringin Dry Powders Production and Characterizationmentioning
confidence: 99%
“…Furthermore, formulation N2 showed a more regular spherical shape in the SEM than formulation C, which exhibited irregular morphology with extensive flat surfaces that may promote a large contact area and would result in increased adhesion between the particles. 41 This increase in adhesion may have reduced the redispersion abilities of the powder and the agglomeration of particles, which should also have increased the MMAD of the aerosol. Finally, the tapped density of formulation C was higher than that of formulation N2 (0.308 g/cm 3 and 0.230 g/cm 3 for formulations C and …”
Section: Evaluation Of Particle Size and In Vitro Lung Depositionmentioning
confidence: 99%
“…Beside conventional spherical particles, spray drying permits also the controlled production of particles of different morphology. Corrugated particles can be attained, for example, by changing the spray drying process conditions [55][56][57], by employing polymeric excipients like dextran to increase the solution viscosity [58] or by adding low soluble components like leucine and trileucine [59][60][61]. These particles have a lower density and thus a larger geometrical size which improves powder dispersibility due to higher drag forces in the air stream.…”
Section: Engineered Particlesmentioning
confidence: 99%